Bury me not in a land of slaves African-Americans in the time of Reconstruction - Hansen, Joyce (Danbury, Conn Franklin Watts, 2000)
An account of African-American life in the period of Reconstruction following the Civil War, based on first-person narratives, contemporary documents, and other historical sources
American Corner
Includes bibliographical references (p. 149-152) and index
11
Keywords: African Americans -- History -- 1863-1877 -- Juvenile literature; African Americans -- Social conditions -- 19th century -- Juvenile literature; African Americans -- Social conditions -- 19th century; Freedmen -- United States -- History -- 19th century -- Juvenile literature; Race relations; Reconstruction (U.S. history, 1865-1877) -- Juvenile literature; Reconstruction (U.S. history, 1865-1877); United States -- Race relations -- Juvenile literature